Technology Of Obtaining and Studying the Process of Green Synthesis of Medicinal Substance with Gold Nanoparticles - Kamal Saidakbarovich, Rizaev; Iroda Bakhtiyor Qizi, Shermatova (Journal of Neonatal Surgery, 2025)
In the work, gold nanoparticles were synthesized using the "Green Synthesis" method with the use of Scutellaria Iscandera L. extracts. The results of the study of gold nanoparticles using the methods of SF spectrophotometry, Inductively coupled plasma mass spectrometry (ICP-MS), and atomic force microscopy (AFM) for visualization of the resulting nanoparticles are presented. The antimicrobial activity of gold nanoparticles was also studied using the microbiological method.